Proposed competency model for technical and vocational education and training (TVET) lecturers teaching in technical colleges, Bauchi State in perspective - Hamisu, Mohammed Adamu; Mohd Salleh, Kahirol; Lai, Chee Sern; Adamu, Babayo Yakubu; Gambo, Kulu (Path of Science, 2017)
Countless issues have been taking place in tertiary institutions including technical colleges of Bauchi State, which give rise to the need for continuous learning and updating competencies of lecturers teaching in technical colleges of all ages. The purpose of this paper is to propose the competency model of TVET lecturers by investigating the competency needs in technical colleges of Bauchi State. Primary data were collected using questionnaires to reveal the perceptions of thirty TVET lecturers based on their competency needs in three categories of technical colleges in Bauchi State. The result shows that the TVET lecturers perceived all the twenty-five competencies as important and the findings also show the accepted Cronbach’s Alpha. The paper concerns on only TVET lecturers perceptions on competency needs in their respective colleges. The paper provides an important pilot analysis on proposed competency model of TVET lecturers to enable further analysis in the area to be carried out.